Citizen Participation in Digitised Environments in Berlin: Visualising Spatial Knowledge in Urban Planning - Ajit Singh; Gabriela Christmann (Urban Planning, 2020)
Digital information and communication technologies influence not only on urban planning but also citizen participation. The increasing level of politically driven involvement of the public in urban planning processes has led to the development of new participatory technologies and innovative visual tools. Using an empirical case study, the article investigates a completed participation process concerning an e-participation platform in Berlin, while focusing on the following questions: (1) How are visualisations communicatively deployed within e-participation formats? (2) In what ways do citizens communicate a kind of spatial knowledge? (3) Which imaginings of public urban space are constructed through the use of visualisations? The exploration of the communication conditions and the `methods' employed will demonstrate the way participants visually communicate their perceptions and local knowledge as well as how they construct their imagining of urban places. In this context, visualisations in participation processes are understood as products of `communicative actions' (Knoblauch, 2019) that allow people to present their visions in ways that are more understandable and tangible to themselves and others. Within this context, by the example of the state-driven e-platform `meinBerlin' a discussion will trace how far digitalised and visualised communicative actions from Berlin residents contribute to the social construction of urban spaces and the extent to which they can be considered a part of cooperative planning.
Keywords: 710; citizen participation; digitised environments; e-participation; meinBerlin; spatial knowledge; urban planning; visual methods; visualisations